Death by meeting a leadership fable-- about solving the most painful problem in business - Lencioni, Patrick (San Francisco Jossey-Bass, 2004)
In his latest page-turning work of business fiction, best-selling author Patrick Lencioni provides readers with another powerful and thought-provoking book, this one centered around a cure for the most painful yet underestimated problem of modern business: bad meetings. And what he suggests is both simple and revolutionary.
Keywords: Business meetings